Returns to franchising - Michael, Steven C.; Moore, Hollie J. (Journal of Corporate Finance, 1995)
The literature on contracts predicts that some principals will pay agents rents, that is, amounts larger than those necessary to keep the agent in the contract. We calculated the earnings of the average franchisee in seventy franchise systems in various industries to determine whether rents are paid as a solution to the agency problem in franchise contracts. We found that many but not all systems paid rents, both ex post and ex ante, to the average franchisee. The results confirm those of Kaufmann and Lafontaine (1994), who found rents associated with McDonald's, but the magnitude of rents within the systems we study was generally much lower than those of McDonald's.